The complement system in innate and adaptive immunity: diseases mediated by the complement system - Sacks, Steven (Henry Stewart Talks, 2021)
Complement deficiency, Organ transplantation, Methods of pathogen evasion of complement, Diseases mediated by complement, SARS-CoV-2 and hyperinflammatory syndrome, Complement and coagulation, Defects in complement regulation, Therapy in complement deficiency